Pengaruh Cashless Society dan Literasi Keuangan terhadap Perilaku Konsumtif Gen Z di Kota Padang - Rahmatika; Ariani, Fatma; Susanti, Rini (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
The purpose of this quantitative research is to understand how the cashless society that has emerged in recent years and financial literacy influence the consumptive behavior of generation z, especially in Padang, West Sumatra. The population chosen was generation z students from Universitas Putra Indonesia YPTK Padang and Politeknik Negeri Padang with a total of 178 respondents. This research applies descriptive statistical analysis techniques through classical assumption tests, multiple linear regression, coefficient of determination, and hypothesis testing. Based on the results of the study, it can be seen that cashless society and financial literacy, both partially and simultaneously, are able to influence the consumptive behavior of generation z.